PERFORMANCE ANALYSIS OF HORIZONTAL IRREGULAR BUILDINGS BASED ON RESPONS SPECTRUM AND TIME HISTORY METHODE - Simbolon, Steffy Catharina Rebeccha; Tampubolon, Sudarno P.; Mulyani, Agnes Sri (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
Indonesia is geographically located in the Pacific Ring of Fire, Especially on Java Island, which has the densest infrastructure and population and is located between the Indo-Australian plate and the Eurasian plate, causing this area to have many active volcanoes and has a high potential for earthquakes. Therefore, it is necessary to pay the planned earthquake load in planning the building structure design to minimize losses due to the earthquake. This study aims to determine the structure’s performance against safeguards, deviations between levels, and structural stability limits against earthquake loads and to review horizontal structural irregularities based on SNI 1726: 2019 regulations in existing buildings at the Simpang Temu MRT Dukuh Atas Jakarta Building. The analysis process was carried out by 3D building modeling using the ETABS software program, analysis based on time history and spectrum response. Time History analysis uses recorded earthquakes of Kobe Japan, ChiChi Taiwan, and El Centro which match the earthquake response spectrum, the results of the analysis based on the program were carried out to compare the two methods used. Based on the results of the analysis, the building is classified into horizontal irregularities with excessive torque ratio > 1.4, average displacement value from the 2nd to 12th floor in the horizontal direction X exceeds the drift value limit. The results of the instability limit for structural stability against displacement based on the P-Delta effect still meet the structural stability limits so it can be stated that the structure is stable and safe.